Polish anthropology on the eve of the new millennium - Drozdowski, Zbigniew (Anthropological Review, 1999)
Author summarizes the main achievements of Polish anthropology in the 20th century, presents the main research problems of this discipline in contemporary Poland and points at the potential dangers which may be faced by Polish anthropology in the forthcoming years.